Preparation and Properties of α‐Cyanoacryloyloxyethoxypropyl‐functionalized MQ Silicone Resin. Issue 34 (8th September 2022) - Liu, Qingyue; Dong, Hong; Zhang, Yipin; Wang, Erlei; Qu, Zhirong; Feng, Qinbang; Wu, Chuan
Abstract: α ‐Cyanoacryloyloxyethoxypropyl‐functionalized MQ resins were synthesized using commercially available hydrogen‐containing MQ silicone resin and 2‐(allyloxy)ethoxytrimethylsilane through a series of hydrosilylation, condensation and retro‐Diels‐Alder reactions. Under the conditions of room temperature and relative humidity of 60 %, the prepared silicone resins could be completely cured within 10 h without adding any promoters. When a small amount of N, N ‐dimethyl‐ p ‐toluidinewas added as an accelerator, the curing time could be shortened to 3–5 s. Although grafted α ‐cyanoacryloyloxyethoxypropyl groups on MQ resins reduced their thermal stabilities, the introduction of α ‐cyanoacryloyloxyethoxypropyl groups destroyed the order of polysiloxane segments and eliminated the crystallization behavior of polysiloxane, which is beneficial to maintain structural stability of the functionalized polysiloxanes over a wide temperature range. The water contact angle of the cured product decreased from 102° to approximately75° when α ‐cyanoacryloyloxyethoxypropyl groups were grafted to the polysiloxaneand thus changed the hydrophobicity of the polydimethylsiloxane materials to hydrophilicity. The novel α ‐cyanoacryloyloxyethoxypropyl‐functionalized MQ resins not only maintain the inherent flexibility of polysiloxanes but also endow the silicone materials with the characteristics of fast cross‐linking. Abstract : The α ‐cyanoacryloyloxyethoxypropyl‐functionalized MQ resins cured completely within 10 h without catalyst or 3 to 5 seconds when promoted by N, N ‐dimethyl‐ p ‐toluidine at room temperature and moderate humidity. The introduced α ‐cyanoacryloyloxyethoxypropyl groups destroyed the order of polysiloxane segments and eliminated the crystallization behavior of polysiloxane, and maintained structural stability over wide temperature ranges.